Determinants of Malnutrition Status Events in Toddlers - Anita Lontaan; Anggeraeni Anggeraeni; Ari Settawati; Mulyanti Mulyanti (Edukasi Ilmiah Indonesia, 2023)
Background: Nutritional needs are very important in helping the growth and development process in infants and children; considering the benefits of nutrients in the body can help the process of growth and development of children. Purpose: Determine the determinants of the incidence of malnutrition status in toddlers. Method: The research design used is analytical descriptive research using the cross-sectional study approach. Results: Statistical tests showed that the diet obtained a calculated p = 0.000 and maternal knowledge p = 0.01. Conclusion: A determinant factor to the incidence of malnutrition in toddlers; is diet and the mother's knowledge level. The nurse's recommendation is expected to increase the provision of counseling to the community, especially for mothers who have toddlers, about the importance of nutrition or nutrition in toddlers in the process of growth and development.